2023
DOI: 10.1039/d2ee03527h
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cation superstructure ordering on oxygen redox stability in O2-type lithium-rich layered oxides

Abstract: Archetypical layered oxide with oxygen redox capability bears additional lithium ion in transition metal layer, and its local coordination with oxygen is crucial in triggering the oxygen redox activity. These...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…For instance, Kang and coworkers reported that the destruction of the honeycomb superstructure in pristine O2-type Li-/Mn-rich layered oxides makes the structure more susceptible to in-plane/out-of-plane TM migrations over cycling and leads to a gradual loss of OAR activity; by contrast, the preservation of the honeycomb superstructure successfully refrains the pernicious TM migrations and achieves a stable OAR activity. 26 In terms of Na layeredoxides, Chueh and others substantiated that the characteristic ffiffi ffi 7 p  ffiffi ffi 7 p superstructure originating from the in-plane &/Mn ordering in Na 2 Mn 3 O 7 (Na 4/7 [& 1/7 Mn 6/7 ]O 2 where & represents TM vacancies) can disfavor O-O dimerization and stabilize the hole polarons on O, which is beneficial to the reversibility of the OAR. [27][28][29] Bruce and colleagues firstly proposed that the ribbon superstructure in P2-Na 0.6 Li 0.2 Mn 0.8 O 2 can hinder the in-plane Mn migration and helps in suppressing the first-cycle voltage hysteresis with respect to the honeycomb superstructure in P2-Na 0.75 Li 0.25 Mn 0.75 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Kang and coworkers reported that the destruction of the honeycomb superstructure in pristine O2-type Li-/Mn-rich layered oxides makes the structure more susceptible to in-plane/out-of-plane TM migrations over cycling and leads to a gradual loss of OAR activity; by contrast, the preservation of the honeycomb superstructure successfully refrains the pernicious TM migrations and achieves a stable OAR activity. 26 In terms of Na layeredoxides, Chueh and others substantiated that the characteristic ffiffi ffi 7 p  ffiffi ffi 7 p superstructure originating from the in-plane &/Mn ordering in Na 2 Mn 3 O 7 (Na 4/7 [& 1/7 Mn 6/7 ]O 2 where & represents TM vacancies) can disfavor O-O dimerization and stabilize the hole polarons on O, which is beneficial to the reversibility of the OAR. [27][28][29] Bruce and colleagues firstly proposed that the ribbon superstructure in P2-Na 0.6 Li 0.2 Mn 0.8 O 2 can hinder the in-plane Mn migration and helps in suppressing the first-cycle voltage hysteresis with respect to the honeycomb superstructure in P2-Na 0.75 Li 0.25 Mn 0.75 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…18b. 82 In addition, the spatial distribution of anionic redoxmediated OVs can also be indirectly imaged by detecting the spatial distribution of TM chemical states in cathode particles. 52,202 However, the widespread use of STXM is limited due to the following shortcomings: long imaging time, imaging in a vacuum, and narrow imaging field.…”
Section: Characterization Of Ovsmentioning
confidence: 99%
“…The strategy of regulating the oxygen framework is widely regarded as a potential solution for addressing the failure of anionic redox reactions. 80–83 In this approach, the O2-type structure, characterized by oxygen atoms arranged in a stacking mode of ABCBA, is utilized to prevent the migration of transition metal ions and associated structural failures. 84 This allows for the achievement of reversible electrochemistry in Li-rich oxide cathodes.…”
Section: Origin and Regulation Of Ovsmentioning
confidence: 99%
See 1 more Smart Citation
“…147 Although trivalent ions may have a weaker impact compared to divalent ions, it has been demonstrated that Co 3+ reduces the electrostatic energy of Li + –Mn 6 4+ ordering by in-plane geometrical frustration. 148 The superstructure can seriously affect the cycle life of the material; it has been shown that even for the same elemental species, different ratios will significantly affect the electrochemical behavior. This is the impact of the control of cation ordering.…”
Section: Building An Appropriate “Transition Metal” (Axm1−xo2) Slab F...mentioning
confidence: 99%